Hidrolisis Protein Isolat Biji Melinjo (Gnetum gnemon L.) menggunakan Alkalase Terimobilisasi dan Aktivitasnya sebagai Antihipertensi (Hydrolysis of Melinjo Seed (Gnetum gnemon L.) Isolated-Protein using Immobilized Alcalase and Its Activity as Antihyper - Nur Fauziah Matra; Endah Puspitasari; Tri Agus Siswoyo (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Hypertension is ranked third on the cause of death in Indonesia for all ages (6.8 %). Protein isolate of melinjo seeds (Gnetum gnemon L.) hydrolyzed with free alcalase has been known to have antihypertensive activity. However, the use of free alcalase is uneconomical since it can only be used once, thus we studied the immobilized alcalase effectivity to hydrolise the melinjo seeds protein isolate to be used as angiotensin converting enzyme (ACE) inhibitor. The immobilization method used entrapment method with DMDMOS/TMOS as matrix. Characterization of the immobilized enzyme was observed by FTIR and effectiveness of repeated hydrolysis was observed by the value of the degree of hydrolysis. The success of the hydrolysis process was determined by SDS-PAGE electrophoresis. Antihypertensive activity test was determined by the ability to inhibit ACE. The results showed that the alcalase has been immobilized in the matrix of silane and SDS-PAGE protein profile showed melinjo seed proteins had been successfully hydrolyzed. Hydrolysis process repeatedly demonstrated that immobilized alcalase was effective to hydrolyze protein isolates of melinjo seeds twice. Based on ACE inhibitory test, there were no significant differences between the protein isolate hydrolyzed by immobilized alcalase (Gg-PH), protein isolates hydrolyzed with free alcalase (Gg-PHB), and captopril. These findings suggest that the antihypertensive activity in Gg-PH is the same with that of captopril. Keywords: hypertension, antihypertensive, melinjo, enzymes immobilization, ACE inhibitor